2007
DOI: 10.1074/jbc.m610626200
|View full text |Cite
|
Sign up to set email alerts
|

Human Polymorphic Variants of the NEIL1 DNA Glycosylase

Abstract: In mammalian cells, the repair of DNA bases that have been damaged by reactive oxygen species is primarily initiated by a series of DNA glycosylases that include OGG1, NTH1, NEIL1, and NEIL2. To explore the functional significance of NEIL1, we recently reported that neil1 knock-out and heterozygotic mice develop the majority of symptoms of metabolic syndrome (Vartanian, V., Lowell, B., Minko, I. G., Wood, T. G., Ceci, J. D., George, S., Ballinger, S. W., Corless, C. L., McCullough, A. K., and Lloyd, R. S. (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 31 publications
8
96
1
Order By: Relevance
“…FapyGua and FapyAde are substrates for mouse and human NEIL1 (27)(28)(29). Importantly, the results presented here demonstrate a functional and physical interaction between CSB and NEIL1 in vivo and in vitro (Figs.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…FapyGua and FapyAde are substrates for mouse and human NEIL1 (27)(28)(29). Importantly, the results presented here demonstrate a functional and physical interaction between CSB and NEIL1 in vivo and in vitro (Figs.…”
Section: Discussionsupporting
confidence: 56%
“…NEIL1 excises 8-OH-Gua very inefficiently (27)(28)(29). Here we observed that at least 4-fold more NEIL1 (100 versus 25 fmol) was required to incise a similar fraction of single-lesion DNA substrates containing 8-OH-Gua as FapyGua or 5-OH-Ura (Fig.…”
Section: -Oh-guamentioning
confidence: 60%
See 2 more Smart Citations
“…If these mouse carcinogenesis studies can be extrapolated to the human populations exposed to various aflatoxins, then deficiencies in the enzymatic activities of NEIL1 may reduce the efficiency of repair of these highly mutagenic adducts. In this regard, others and we have previously carried out biochemical characterization of several NEIL1 polymorphic variants (37,38). When expressed as purified proteins, two of the variants, G83D and C136R, showed little to no DNA glycosylase activity.…”
Section: Discussionmentioning
confidence: 99%